The chemical and biological investigation of Philippine and Okinawan seaweeds with special emphasis on Sargassum crassifolium J. Agardh (Fam. Sargassaceae) - Sua, Irene (Yap) 1964-
Twenty different seaweeds from Philippine and Okinawan waters were collected and tested for the presence of halogens and for antimicrobial activity. The crude ethyl acetate-soluble extract of the twenty seaweeds was also subjected to proton magnetic resonance spectroscopy. Emphasis was given to the brown alga Sargassum crassifolium J. Agardh (Fam. Sargassaceae). Different methods of separation were conducted, to which one of the methods yielded a sugar alcohol. Structure elucidation and characterization of the isolated compound were done by infrared spectroscopy, proton magnetic resonance spectroscopy, and 13C NMR spectroscopy. The isolated compound, mannitol, was subjected to antimicrobial activity screening and to germination inhibition activity test. It was found to be active against Trichoderma sp. at a concentration of 120 mg/ml, but was not active against other bacteria and fungi tested. In the germination inhibition activity test, it was found that mannitol possesses minimal germination activity against the seeds of Raphanus sativus L. and Brassica napus L.
Available to the general public.
Thesis (Master of Science in Pharmacy)--University of the Philippines Manila, October 1990.
Keywords: Marine algae; Sargassum